EFFECTS OF MULTIMODAL LITERACY ON INTRINSIC AND EXTRINSIC MOTIVATION AMONG STUDENTS FROM PERIPHERAL AREAS - Lestari, Jesinta Dwi; Mufaridah, Fitrotul; Fadlillah, Anam (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Addressing low student engagement is critical, particularly in peripheral schools serving low socioeconomic status (SES) populations. This study aims to investigate the effect of multimodal literacy on students' motivation to learn English in a school with a low socioeconomic background. Using a mixed-methods strategy with a quasi-experiment pre-post design, 39 students participated in learning with multimodal literacy in three weeks of interventions. Students' motivation was measured before and after the intervention using a questionnaire adapted from the Attitude/Motivation Test Battery (AMTB). Results of the t-test showed a slight: 0.176 in intrinsic and -.956 in extrinsic. Intrinsic motivation showed no significant difference, and extrinsic motivation saw a statistically non-significant increase. Qualitative observations showed off-task behavior, low self-regulation, or inconsistent engagement. The extrinsic factors, multimodality and socioeconomic background, influenced students’ motivation simultaneously. This study concludes that short-term interventions using multimodal media have not been able to sustainably effect motivation. This non-significant effect emphasizes the importance of long-term strategies and family involvement as the necessary next steps for practitioners and policymakers in peripheral areas to capture the more stable impact of multimodality on students' internal and external motivation.